Does environmental knowledge moderate the relationship between household determinants' intention to practice solid waste segregation-at-source? a conceptual paper - Cheng, K. W.; Osman, S.; Jusoh, Z. M.; Lau, J. L. (Universiti Putra Malaysia Kampus Bintulu Sarawak, 2020)
Previous research has reported that environmental knowledge plays an important role in enhancing general pro-environmental behaviour, as environmental knowledge appears to be the key indicator for increasing awareness of several pollution promulgations and other natural environmental issues. However, the significant role of environmental knowledge in the intention of households to practise solid waste segregation-at-source is not well understood. This research will, therefore, investigate the influence of environmental knowledge on the intention of households to engage in solid waste segregation-at-source. Further analysis will also be carried out explore the moderating effect of environmental knowledge in the relationship between the households’ attitude and subjective norm (i.e. descriptive norm and injunctive norm) with the intention to practise solid waste segregation-at-source. The findings of this current research are expected to provide an essential opportunity to investigate knowledge gaps, to contribute to the enrichment of existing literature, as well as to provide important insights for local households and Malaysian government agencies to strengthen the sense of responsibility for environmental cleanliness.